1986
DOI: 10.7326/0003-4819-104-5-644
|View full text |Cite
|
Sign up to set email alerts
|

Risk of Nosocomial Infection with Human T-Cell Lymphotropic Virus Type III/Lymphadenopathy-Associated Virus in a Large Cohort of Intensively Exposed Health Care Workers

Abstract: To assess the risk of nosocomial transmission of human T-cell lymphotropic virus type III/lymphadenopathy-associated virus (HTLV-III/LAV), we prospectively evaluated a cohort of 531 health care workers. One hundred fifty of these employees reported percutaneous or mucous membrane exposures to blood or body fluids from a patient with the acquired immunodeficiency syndrome (AIDS) during the treatment of 238 such patients since 1981. None of these 150 employees had serologic evidence of HTLV-III/LAV infection on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
21
0

Year Published

1988
1988
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 196 publications
(21 citation statements)
references
References 11 publications
0
21
0
Order By: Relevance
“…The incidence of needle-stick injury is surprisingly high [4][5][6]. In one study, 16 of 86 junior doctors (19%) had suffered injury from a needle which was contaminated with the blood of HIV-positive patients [4].…”
mentioning
confidence: 99%
“…The incidence of needle-stick injury is surprisingly high [4][5][6]. In one study, 16 of 86 junior doctors (19%) had suffered injury from a needle which was contaminated with the blood of HIV-positive patients [4].…”
mentioning
confidence: 99%
“…Other diseases that can be acquired as a result of occupational exposures to blood include malaria, 2 tuberculosis, 3 rocky mountain spotted fever, 4 herpes zoster, 5 lassa fever, 6 cryptococcus, 7 non-A-non-B hepatitis 8 and hepatitis A. 9 The risk of health workers acquiring these diseases increases with increase in incidence of the mechanical hazards.…”
Section: Introductionmentioning
confidence: 99%
“…12 One hundred and fifty of a cohort of 531 health care workers followed up in the United States of America reported percutaneous or mucous membrane exposure to blood or body fluids from a patient with AIDS during the treatment of 238 of such patients. 8 Momah 13 in her study of the epidemiology of needle stick and sharp injuries among health care workers in Nigerian hospitals found that 84.2% of the respondents had experienced at least one injury since embarking on their respective careers, while 62.2% of them sustained their recent injury within the past one year. Doctors and nurses from two hospitals were followed up for two three-monthly periods to ascertain the occurrence of injuries 13 and the survey revealed high incidence rate of 3.9 per person years (ppy) and 2.2 ppy for the first and second quarters respectively.…”
mentioning
confidence: 99%
“…States of America and it reported percutaneous or mucous membrane exposure to blood or body fluids from a patient with AIDS during the treatment of 238 of such patients [16] . Similarly, according to a Tanzanian study, five health care workers per year experienced percutaneous injuries [17] .…”
Section: Introductionmentioning
confidence: 99%